Cloning and expression of trehalose‐6‐phosphate synthase 1 from Rhizopus oryzae. (16th November 2015) - Ozer Uyar, Ebru; Yücel, Meral; Hamamcı, Haluk
Abstract : Trehalose is a reducing disaccharide acting as a protectant against environmental stresses in many organisms. In fungi, Trehalose‐6‐phosphate synthase 1 (TPS1) plays a key role in the biosynthesis of trehalose. In this study, a full‐length cDNA from Rhizopus oryzae encoding TPS1 (designated as RoTPS1 ) was isolated. The RoTPS1 cDNA is composed of 2505 nucleotides and encodes a protein of 834 amino acids with a molecular mass of 97.8 kDa. The amino acid sequence of RoTPS1 has a relatively high homology with the TPS1s in several other filamentous fungi. RoTPS1 was cloned into Saccharomyces cerevisiae and secretively expressed.